1990
DOI: 10.1093/jn/120.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Selenite Supplementation on Selenium Excretion and Organ Accumulation in Rats

Abstract: We examined the effect of chronic selenite supplementation on whole body and selected organ selenium (Se) accumulation, urine excretion of total Se and trimethylselenonium ion, and Se balance in adult male rats. Animals were housed in metabolic cages and given either deionized water or water containing 4 micrograms of Se/mL as selenite for 30 d. Absorption of selenite was nearly complete, with only approximately 10% of ingested Se appearing in feces. There was a rapid rise in urinary Se that reached a plateau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Gaseous exhalations of Se are discussed as an additional excretion pathway of Se (G anther et al 1966; J anghorbani et al 1990). However, Se exhalations were not of quantitative importance in the present experiment since the injected 75 Se was recovered completely irrespective of the level of Se supply.…”
Section: Discussionmentioning
confidence: 99%
“…Gaseous exhalations of Se are discussed as an additional excretion pathway of Se (G anther et al 1966; J anghorbani et al 1990). However, Se exhalations were not of quantitative importance in the present experiment since the injected 75 Se was recovered completely irrespective of the level of Se supply.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, approximately 90% absorption of selenite by male Sprague Dawley rats was reported, with only 10% of the ingested selenium being detected in the faeces (Janghorbani et al, 1990). A similar degree of absorption was reported in mice and dogs.…”
Section: Bioavailabilitymentioning
confidence: 62%
“…Selenium status is known to change with age, in particular, a decline in selenium status has been documented in the elderly, 49,50 and rats appear to adapt in response to long-term selenium supplementation. 46,51 The interest in long-term selenium supplementation as a chemoprevention measure, 52 or short to medium-term treatment with selenium as an adjuvant therapy, 53,54 requires more investigations of the changes of selenium status and speciation with age and duration of selenium supplementation.…”
Section: Resultsmentioning
confidence: 99%